2005
DOI: 10.1016/j.cplett.2005.02.088
|View full text |Cite
|
Sign up to set email alerts
|

Strains induced in carbon nanotubes due to the presence of ions: Ab initio restricted Hatree–Fock calculations

Abstract: Motivated by the experimental demonstration of the actuator action of single-walled carbon nanotubes and in situ resonance Raman experiments, we have performed ab initio restricted Hatree-Fock calculations of the electronic structure of a (5,5) singlewalled nanotube in the presence of various ions. We show that the presence of ions near the nanotube causes combined axial and radial deformations of the nanotube. The presence of ions causes a small charge transfer from the ions to the nanotubes as well as change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…To be more specific, the solvent molecules that had self-assembled into a 2D monolayer annular coating around the CNT would experience a pinning potential towards the nanotube surface, [117] exerted by the adsorbed ionic species (e.g., depicted here as cations, without loss of generality, Fig. 3a).…”
Section: Stick-slip Thermal Activation 222mentioning
confidence: 99%
“…To be more specific, the solvent molecules that had self-assembled into a 2D monolayer annular coating around the CNT would experience a pinning potential towards the nanotube surface, [117] exerted by the adsorbed ionic species (e.g., depicted here as cations, without loss of generality, Fig. 3a).…”
Section: Stick-slip Thermal Activation 222mentioning
confidence: 99%
“…One material with the potential to meet these challenging aims was randomly discovered in experiments as flexible electrodes for EAP applications. A paper of randomly oriented carbon nanotubes showed active strain at low activation voltage 5 of < ±5V in combination with theoretically high achievable active strains 1% 6,7 . Further research on CNTs as actuators is inspired by their extraordinary electro-mechanical properties such as Young's modulus of 1TPa 8 or the thermal and electrical conductivities 9 (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Binding energies tend to depend on the configuration, i.e., on being odd or even for the chiral vector (m,0), rather than on the diameter size. Sood et al [29] theoretically showed that the presence of ions near the armchair CNT causes a small charge transfer from the ions to the nanotubes as well as changes the p-p overlap energy. They found that the developed strains are primarily due to the electrostatic interactions with only a small contribution from the charge transfer.…”
Section: Introductionmentioning
confidence: 99%